Iron deficiency anemia: detection in the clinical laboratory, using the biochemical ferritin marker - Becerra-Nazareno, Sabrina Mercedes (2022)
The general objective of this study was to provide an analysis from a simple approach to the detection of iron deficiency or iron deficiency anemia, in the clinical laboratory, using the biochemical marker ferritin. To achieve this task, a documentary-bibliographic investigation was proposed, with a methodology framed in content analysis. For the selection of the consulted material, criteria such as original and review studies published in Spanish, contributions and year of publication corresponding to the period 2016-2021 were assumed. However, works from previous years were referenced as they were considered valuable for this research. Among the main conclusions, it was found that: anemia due to iron (Fe) deficiency or iron deficiency has been classified as a global public health problem, since it affects millions of people around the world, both in developed and emerging countries, mainly affecting to children, adolescents and pregnant women. Therefore, one of the objectives of the WHO is to reduce anemia to eradicate all forms of malnutrition. In response to this, in recent years the clinical laboratory has incorporated new biomarkers to those traditionally used, in order to improve their contribution to the diagnosis and monitoring of iron deficiency and, one of the most reliable laboratory methods to determine the lack of Iron in the body is the measurement of the level of ferritin, since its value is usually below the normal range in patients with iron deficiency anemia.